Pengaruh Latihan Medicine-ball Push Throw and Sprint dengan Rotational Medicine-ball Throw and Sprint Terhadap Peningkatan Sprint dan Power Lengan - Ramdan, Mochamad Faisal; Rustiawan, Hendra; Sudrazat, Adang (Jurnal Keolahragaan, 2024)
Changes for the better in sprinting and arm power are the goals resulting from treatment of medicine-ball push throw and sprint exercises with rotational medicine-ball throw and sprint. Research method of pre-experiment. The location was at the Bared FC football field in Banjar City. The selection of players used all 20 players aged 16-17 years. The test given was throwing a medicine ball over the head. The data processing process uses SPSS series 24. The results: 1. There was a positive influence on medicine-ball push throw and sprint as a result of sprint speed and arm power in Bared FC football players in Banjar City. 2. There was a positive influence on rotational medicine-ball throw and sprint as a result of sprint speed and arm power in Bared FC football players in Banjar City. 3. There was a better difference between medicine-ball push throw and sprint training and rotational medicine-ball throw and sprint training on the results of sprint speed and arm power in Bared FC football players in Banjar City. Conclusion: Medicine-ball push throw and sprint training with rotational medicine-ball throw and sprint training increases sprint speed and arm power in Bared FC football players in Banjar City. Suggestion: When carrying out training or teaching medicine-ball push throw and sprint movements with rotational medicine-ball throw and sprint movements at the beginner level, they must be closely supervised by a football coach who really knows the rules of good and correct training.Perubahan menjadi lebih baik untuk lari sprint dan power lengan adalah tujuan hasil dari perlakuan latihan medicine-ball push throw and sprint dengan rotational medicine-ball throw and sprint. Pre-eksperimen yang digunakan sebagai metode penelitian studi ini. Lokasinya di lapangan sepakbola Bared FC Kota Banjar. Pemilihan pemain menggunakan seluruh pemain yang berusia 16-17 tahun sebanyak 20 orang. Tes yang diberikan yaitu lemparan bola medicine di atas kepala. Proses pengolahan data menggunakan SPSS serie 24. Hasil studi yaitu: 1. Adanya pengaruh yang positif untuk medicine-ball push throw and sprint  hasil dari kecepatan sprint dan power lengan pada pemain sepakbola Bared FC Kota Banjar. 2. Adanya pengaruh yang positif untuk rotational medicine-ball throw and sprint hasil dari kecepatan sprint dan power lengan pada pemain sepakbola Bared FC Kota Banjar. 3. Ada perbedaan yang lebih baik antara latihan medicine-ball push throw and sprint  dan latihan rotational medicine-ball throw and sprint hasil dari kecepatan sprint dan power lengan pada pemain sepakbola Bared FC Kota Banjar. Kesimpulan: Medicine-ball push throw and sprint dan rotational medicine-ball throw and sprint hasil dari kecepatan sprint dan power lengan pada pemain sepakbola Bared FC Kota Banjar. Saran: medicine-ball push throw and sprint  dengan gerakan rotational medicine-ball throw and sprint dapat dijadikan sebagai latihan lari cepat dan lemparan bola dengan tujuan memiliki lemparan bola yang masimal serta kecepatan lari yang baik.